Contemporary issues in global criminal justice - Johnston, Ed; Marsh, Sophie (Lexington Books, 2022)
The importance of protecting sex workers from harm by Sophie Marsh -- The impact of the judicial role on treatment and punishment in the New Zealand Alcohol & Other Drug Treatment Court by Toni Carr -- Stop and search powers in England & Wales : the commissioner, the home secretary, the media and the public by Jack James and Richard Hester -- Reform of police interrogations in Croatia : endangering the efficiency of the criminal justice system by Elizabeta Ivičević Karas and Zoran Burić -- The risks of risk aversion : trajectories of automation in policing by Mehzeb Chowdhury -- Artificial Intelligence and the use of algorithms in the criminal judicial system,Chimera or Panacea? by Raquel Borges Blázquez -- The vulnerable accused in Scotland : 'a fig for those by law protected'? by Eamon P. H. Keane -- The group decision-making of the jury : challenges to a fair trial by Sarah Lloyd -- Victim participation as a right : from the International Criminal Court to the European Court of Human Rights by Freya Doughty -- Out-of-court disposals in the Dutch criminal process : an affront to a fair trial? by Anna Pivaty -- The over-representation of Aboriginals in Canadian correctional facilities : an issue before Canada by Eric Myles -- Contemporary issues in the penitentiary system of the Republic of Macedonia : fundamentals of criminal justice reform and penitentiary reform by Gordana Lažetić and Elena Mujoska-Trpevska.